Large crowd viewing races on Front St. for July 4th celebration, Dawson, Yukon Territory, 1899. - Hegg, Eric A., 1867-1948 (1899)
Caption on image: "Front Street Dawson July 4th 1899" No. 6 appears in lower right corner"